(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
A total of 125 angiosperms under 103 genera and 52 families have been recorded from Daulatpur Upazila in Kushtia. Magnoliopsida is represented by 41 families, 73 genera and 86 species, whereas Liliopsida is represented by 11 families, 30 genera and 39 species. In Liliopsida, Poaceae appears to be the largest family comprising 15 genera and 20 species. In Magnoliopsida, Euphorbiaceae appears to be the largest family comprising 9 genera and 14 species. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15320 J. Asiat. Soc. Bangladesh, Sci. 38(1): 53-65, June 2012